Rancang Bangun Low Power Sensor Node Menggunakan MSP430 Berbasis NRF24L01 - Rizky Putra Pratama; Sabriansyah Rizqika Akbar; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Communication technology is now very grown even more with their wireless technology. This technology is very popular due to their ability to transmit data or information wirelessly. One of the utilization of wireless technology is the Wireless Sensor Network. In the Wireless Sensor Network, the data transmission between sensor nodes is highly dependent on the power source in the form of batteries which have a limited capacity, this can cause problems because the sensor nodes are required to be able to survive as long as possible. To overcome the problem of resource savings, research on low-power mode in Wireless Sensor Network technology that is by applying the mechanism of sleep mode at the sensor node that resources can the battery last longer. In accordance with the above problems, the author makes the design of sensor nodes using MSP430 microcontroller which will regulate all the processes on the node, including regulating the use sleep mode as a way of saving power supply. For data transmission, the system uses NRF24L01 as communication modules. The data is sent in the form of calculation of the temperature of the LM35 temperature sensor. The results of the study in terms of the use of power-saving sleep mode can be used by the nodes. This is evidenced by the saving power used by the nodes without using sleep mode with nodes that use sleep mode reaches 33.31%. The accuracy of data transmission in this study was divided into two, the data transmission without hindrance average accuracy of data transmission up to 100%. While the data transmission with the hindrance an average accuracy of the data transmission only reached 87.7%.